Development of a co-culture system for green production of caffeic acid from sugarcane bagasse hydrolysate - Wang, Xihui; Zhao, Cui; Lu, Xinyao; Zong, Hong; Zhuge, Bin (Frontiers in Microbiology, 2024)
Caffeic acid (CA) is a phenolic acid compound widely used in pharmaceutical and food applications. However, the efficient synthesis of CA is usually limited by the resources of individual microbial platforms. Here, a cross-kingdom microbial consortium was developed to synthesize CA from sugarcane bagasse hydrolysate using Escherichia coli and Candida glycerinogenes as chassis. In the upstream E. coli module, shikimate accumulation was improved by intensifying the shikimate synthesis pathway and blocking shikimate metabolism to provide precursors for the downstream CA synthesis module. In the downstream C. glycerinogenes module, conversion of p-coumaric acid to CA was improved by increasing the supply of the cytoplasmic cofactor FAD(H2). Further, overexpression of ABC transporter-related genes promoted efflux of CA and enhanced strain resistance to CA, significantly increasing CA titer from 103.8 mg / L to 346.5 mg/L. Subsequently, optimization of the inoculation ratio of strains SA-Ec4 and CA-Cg27 in this cross-kingdom microbial consortium resulted in an increase in CA titer to 871.9 mg/L, which was 151.6% higher compared to the monoculture strain CA-Cg27. Ultimately, 2311.6 and 1943.2 mg/L of CA were obtained by optimization of the co-culture system in a 5-L bioreactor using mixed sugar and sugarcane bagasse hydrolysate, respectively, with 17.2-fold and 14.6fold enhancement compared to the starting strain. The cross-kingdom microbial consortium developed in this study provides a reference for the production of other aromatic compounds from inexpensive raw materials.